2016
DOI: 10.1556/2006.5.2016.077
|View full text |Cite
|
Sign up to set email alerts
|

Targeted exome sequencing for the identification of a protective variant against Internet gaming disorder at rs2229910 of neurotrophic tyrosine kinase receptor, type 3 (NTRK3): A pilot study

Abstract: Background and aimsInternet gaming disorder (IGD) has gained recognition as a potential new diagnosis in the fifth revision of the Diagnostic and Statistical Manual of Mental Disorders, but genetic evidence supporting this disorder remains scarce.MethodsIn this study, targeted exome sequencing was conducted in 30 IGD patients and 30 control subjects with a focus on genes linked to various neurotransmitters associated with substance and non-substance addictions, depression, and attention deficit hyperactivity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…However, studies determining the genetic factors of GD for a designed intervention are scarce. Until now, only two studies have demonstrated associations of the C allele of rs1044396 in the nicotinic acetylcholine receptor alpha 4 subunit (CHRNA4) [ 2 ] and rs2229910 of NTRK3 [ 3 ] with IGD. Further research to evaluate the associations between polymorphisms and their associated factors is necessary for intervention design.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies determining the genetic factors of GD for a designed intervention are scarce. Until now, only two studies have demonstrated associations of the C allele of rs1044396 in the nicotinic acetylcholine receptor alpha 4 subunit (CHRNA4) [ 2 ] and rs2229910 of NTRK3 [ 3 ] with IGD. Further research to evaluate the associations between polymorphisms and their associated factors is necessary for intervention design.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of genetic features, IGD associations with personality traits, such as sensation-seeking [ 12 ], impulsivity [ 13 ], and self-control [ 14 ], have been identified. In addition, several association studies showed that the Taq1A1 allele of the dopamine receptor gene ( DRD2 ) [ 15 ], the methionine variant of dopamine degradation enzyme gene ( COMT ) [ 15 ], short allelic variants of the serotonin transporter gene ( 5-HTTLPR ) [ 16 ], and polymorphisms of the nicotinic acetylcholine receptor gene ( CHRNA4 ) [ 17 ] and neurotrophic tyrosine kinase type 3 receptor gene ( NTRK3 ) [ 18 ] were associated with PIU. These personality traits and polymorphisms have also been shown to influence diverse substance addictions [ 19 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tras el análisis de los estudios se identifican seis factores que pueden influir en el IGD, como son los factores ambientales (Hong et al, 2019), sociodemográficos (Männikkö et al, 2018), variantes genéticas (Kim et al, 2016), psicosociales, las relaciones familiares y el perfil de los menores diagnosticados con IGD.…”
Section: Factores Asociados Al Igdunclassified